2017
DOI: 10.1016/j.coi.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Immune development and environment: lessons from Amish and Hutterite children

Abstract: Children who grow up in traditional farm environments are protected from developing asthma and allergy. This “farm effect” can be largely explained by the child’s early life contact with farm animals, in particular cows, and their microbes. Our studies in Amish and Hutterite school children living on farms in the U.S. have further demonstrated that this protection is mediated through innate immune pathways. Although very similar with respect to ancestry and many lifestyle factors that are associated with asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 73 publications
0
53
2
Order By: Relevance
“…Recent clinical evidence has suggested that people exposed to “barn dust” in early life are also protected against allergic diseases and asthma, an observation supported by the demonstration that mice chronically exposed to low doses of endotoxin‐rich environments such as farm dust are protected against the development of allergic lung inflammation in response to HDM by a TLR‐4‐mediated mechanism . TLR‐4 signalling in the lung leads to translocation of NF‐κB, increasing the expression of attenuators of this response such as the ubiquitin‐modifying enzyme A20 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical evidence has suggested that people exposed to “barn dust” in early life are also protected against allergic diseases and asthma, an observation supported by the demonstration that mice chronically exposed to low doses of endotoxin‐rich environments such as farm dust are protected against the development of allergic lung inflammation in response to HDM by a TLR‐4‐mediated mechanism . TLR‐4 signalling in the lung leads to translocation of NF‐κB, increasing the expression of attenuators of this response such as the ubiquitin‐modifying enzyme A20 .…”
Section: Discussionmentioning
confidence: 99%
“…Seminal epidemiologic studies in European children raised in farming and non‐farming environments have clearly demonstrated the connection between early life exposure to traditional farms and decreased prevalence of allergic diseases and asthma, a pattern referred to as the “farm effect” . Specific exposures that contribute to the farm effect include contact with livestock (cattle, pigs and poultry) and animal feed (hay, grain and straw), consumption of raw milk, high endotoxin levels and environmental microbes . More recent data have clarified the reach of protective exposures by showing that physical proximity to a traditional farm within a maximum radius of 100 m is inversely associated with childhood asthma and atopic sensitization …”
Section: Role Of Innate Immunity In Asthma Protectionmentioning
confidence: 99%
“…[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Specific exposures that contribute to the farm effect include contact with livestock (cattle, pigs and poultry) and animal feed (hay, grain and straw), consumption of raw milk, high endotoxin levels and environmental microbes. [61][62][63] More recent data have clarified the reach of protective exposures by showing that physical proximity to a traditional farm within a maximum radius of 100 m is inversely associated with childhood asthma and atopic sensitization. 64 A remarkable example of the farm effect is offered by children raised in Amish traditional farming communities 65 and their comparison with Hutterite children.…”
Section: The Farm Effect: Epidemiology and Immunologymentioning
confidence: 99%
“…Epidemiological studies have repeatedly and clearly identified environmental exposures that prevent early-life asthma development. The most striking data come from farmyard studies, initially from Europe, and more recently from farming communities in North America [52], which have convincingly shown that growing up on a farm with traditional, but not industrialized farming, protects from the development of early-onset asthma, even in children with similar genetic backgrounds [53]. Moreover, studies have been undertaken in Amish and Hutterite families, both of which have very similar genetic ancestry and agricultural lifestyles in America but have distinct farming practices.…”
Section: Trends In Immunologymentioning
confidence: 99%